2022
DOI: 10.1177/13621688211072381
|View full text |Cite
|
Sign up to set email alerts
|

Test preparation pedagogy for international study: Relating teacher cognition, instructional models and academic writing skills

Abstract: There now exists an established body of work outlining the challenges international students can face as part of the acculturation process, including a range of academic and non-academic pressures to overcome. For many students, writing essays in academic English for the first time is problematic. This article considers pedagogical approaches for IELTS writing test preparation prior to university admission, and the potential for introducing academic writing skills at an earlier stage of students’ learning. Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…EAP courses teach academic writing skills preentry, but many students enter university courses directly if their IELTS score meets stipulated requirements, effectively bypassing a highly useful step in early academic writing acquisition (Clark 2018). This further highlights the importance of the test preparation stagefor these students test preparation's introduction to academic writing expectations may be all that they encounter before starting their course (Clark and Yu 2022).…”
Section: The Relationship Between Ielts and Subsequent Academic Writingmentioning
confidence: 94%
See 1 more Smart Citation
“…EAP courses teach academic writing skills preentry, but many students enter university courses directly if their IELTS score meets stipulated requirements, effectively bypassing a highly useful step in early academic writing acquisition (Clark 2018). This further highlights the importance of the test preparation stagefor these students test preparation's introduction to academic writing expectations may be all that they encounter before starting their course (Clark and Yu 2022).…”
Section: The Relationship Between Ielts and Subsequent Academic Writingmentioning
confidence: 94%
“…Selection of test preparation approaches (such as those outlined above) rests on teacher cognition (Clark and Yu 2022); the pedagogical experiences and training that a teacher encounters necessarily shapes his or her classroom approach (Irvine-Niakaris and Kiely 2015). Irvine-Niakaris and Kiely's study investigated teacher use of strategies for reading test preparation, revealing that established approaches (e.g., pre-reading tasks) were beneficial to students even though teacher interpretation of the method varied.…”
Section: Identifying Teaching Approaches That May Promote Test Score ...mentioning
confidence: 99%
“…While role-playing activities and cultural immersion exercises garnered significant adoption, their slightly lower perceived effectiveness raises questions about the alignment between usage and impact (Brown, 2018). This incongruity could be attributed to variations in instructional approaches, highlighting the need for a nuanced exploration of how these strategies are implemented in different contexts (Clark, 2020).…”
Section: Cross-sectional Analysismentioning
confidence: 99%
“…Numerous empirical studies 57 , 60 , 61 have examined the complex interplay between teachers’ implicit cognition and explicit practices, suggesting the significant role cognition plays in shaping their instructional practices. However, more studies 62 , 63 have reported a distinctive discordance between teachers’ cognition and practices and identified a series of influential factors that mediate the cognition-practice relationship.…”
Section: Literature Reviewmentioning
confidence: 99%